2015
DOI: 10.1007/s00268-015-2946-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Laparoscopic Hepatectomy for Hepatocellular Carcinoma in the Posterosuperior Liver Segments

Abstract: LH is safe and feasible for selected patients with HCC in the posterosuperior segments of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…Long-term results show that oncological benefits of a laparoscopic approach are similar to open surgery [23][24][25]. With the improvement in laparoscopic [6,7] and the accumulation of clinical experience in laparoscopic and hepatic surgery, the indications for laparoscopic liver resection are expanding, including the type of resection and the size or location of the tumor [26,27]. Although many limitations have been overcome, bleeding is still the most important problem that hinders the development of laparoscopic liver resection.…”
Section: Discussionmentioning
confidence: 97%
“…Long-term results show that oncological benefits of a laparoscopic approach are similar to open surgery [23][24][25]. With the improvement in laparoscopic [6,7] and the accumulation of clinical experience in laparoscopic and hepatic surgery, the indications for laparoscopic liver resection are expanding, including the type of resection and the size or location of the tumor [26,27]. Although many limitations have been overcome, bleeding is still the most important problem that hinders the development of laparoscopic liver resection.…”
Section: Discussionmentioning
confidence: 97%
“…Laparoscopic hepatectomy was performed according to the Chinese expert consensus on laparoscopic hepatectomy and the relevant surgical guidelines. A detailed description of patient positioning and trocar locations has been reported previously. Intraoperative ultrasonography (Toshiba, Hitachi, Tokyo, Japan) was used to identify the location and size of the tumour, its relationships with the major intrahepatic ducts, the location of main intrahepatic ducts on the liver parenchymal transection plane, and to search for any metastatic site in other parts of the liver or tumour thrombus in the portal vein and/or hepatic vein.…”
Section: Methodsmentioning
confidence: 99%
“…Tumour size and location are two important factors in determining the indications for laparoscopic hepatectomy in patients with HCC. Some studies have shown that laparoscopic hepatectomy can be undertaken in patients with HCC located in the posterosuperior liver segments (segments I, IVa, VII and VIII). However, whether a large tumour size is a contraindication to laparoscopic hepatectomy remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Araki et al proved the feasibility of the approach of caudate lobe resections by analyzing such cases around 14 years from 2000 to 2014 (23). Evidence from multicenter suggested that LLR for posterosuperior parts of the liver was feasible and safe (24)(25)(26). In addition, the authors pointed out that surgical techniques must be individualized according to the tumor location and its relationship to the major hepatic vessels.…”
Section: Location Of the Tumormentioning
confidence: 99%